2019
DOI: 10.3390/mi11010036
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Based Three-Dimensional Co-Culture Model for Long-Term Hepatotoxicity Prediction

Abstract: We developed concave microwell arrays to establish a size-controllable 3-D co-culture liver model for in vitro drug toxicity testing, to predict hepatotoxicity. The interaction of hepatocytes with hepatic stellate cells (HSCs) was investigated by co-culturing primary 3-D hepatocyte spheroids and HSCs (heterosphere), using 3-D liver-on-a-chip. The effect of HSCs was investigated during spheroid formation; they were involved in controlling the organization of spheroidal aggregates and the formation of tight cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The liver plays a principal role in the digestion, metabolism and detoxification of xenobiotic compounds 36 . Drug‐induced liver injury (DILI), which leads to liver failure and drug attrition, 37 is the major cause of the withdrawal of approved drug compounds from the market 38 .…”
Section: Platforms For Drug Toxicity Assessment/drug‐drug Interaction (Ddi) Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The liver plays a principal role in the digestion, metabolism and detoxification of xenobiotic compounds 36 . Drug‐induced liver injury (DILI), which leads to liver failure and drug attrition, 37 is the major cause of the withdrawal of approved drug compounds from the market 38 .…”
Section: Platforms For Drug Toxicity Assessment/drug‐drug Interaction (Ddi) Analysismentioning
confidence: 99%
“…The heterospheres formed as a result of a co‐culture demonstrated higher CYP activity than hepatospheres upon treatment with acetaminophen, and the experiments with repeated exposure of the spheroids to acetaminophen and isoniazid show more stable IC 50 values in heterospheres. These results suggest that the system is an optimized tool for drug toxicity studies, and due to improved metabolic competence is suitable for investigating drug‐drug interactions (DDIs) 36 …”
Section: Platforms For Drug Toxicity Assessment/drug‐drug Interaction (Ddi) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, spheroids remain difficult to form with > 50% of PHH donors, 34 potentially due to variable ECM secretion rates across cells from different donors. This issue can be mitigated with the incorporation of liver and nonliver NPCs with hepatocytes toward improving spheroid formation efficiency, 38,39 potentially due to augmented ECM deposition from the NPCs. Additionally, the coculturing of hepatocytes with liver NPCs facilitates the study of how multiple liver cells affect disease progression, highlighted in later sections.…”
Section: Self-assembled 3d Spheroids and Organoidsmentioning
confidence: 99%
“…Several studies have reported the use of spheroids to study hepatic cells, including cultures of hepatocytes only, as well as coculture studies with HSCs and Kupffer cells. One study reported the creation of a 3D hepatocyte/HSC coculture spheroid using low-adhesion poly-DL-lactide [9]. Another study reported that the coculture system suitably mimicked the in vivo environment, showing utility for the prediction of in vivo hepatotoxicity [10].…”
Section: Introductionmentioning
confidence: 99%